Perancangan Sign System Wisata Agro Lembah Kecubung - Ade Hilal Putra Dewanda; Aninditya Daniar (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
Agro Tourism Lembah Kecubung is a family tourist spot that operates in the field of agrotourism with the themes of nature tourism, educational tourism and food security. Amethyst Valley is located in Penanggungan Village, Trawas District, Mojokerto Regency. This location is located at the foot of Mount Penanggungan which is rich in rice fields and plantations. The focus of tourist attractions lies in cultivating various food security such as vegetables, fish, cattle, etc. Apart from that, the Amethyst Valley also provides other tourist destinations such as restaurants, fish therapy and refugia flower gardens. With so many destinations on offer, the placement of these various destinations is quite complicated, so a sign system is needed to support the provision of tourist facilities and visitor mobility. The sign system provided is a vital sign system such as directions and place names. . With a sign system, it is easier for visitors to determine, search for and find out where the destinations and places they want to go.